Catheter ablation of the mitral isthmus line using the novel DiamondTemp ablation system: first experience using two different ablation protocols. (19th May 2022) - Rottner, L; Schleberger, R; Lemoine, M; My, I; Moser, F; Moser, J; Dinshaw, L; Kirchhof, P; Ouyang, F; Rillig, A; Metzner, A; Reissmann, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Mitral ishmus ablation is an established approach to treat perimitral reentrant tachycardia, and is often performed as substrat modification in patients with persistent atrial fibrillation (AF). Bidirectional block of the mitral isthmus line (MIL) is still a great challenge using conventional ablation catheters, but is essential to prevent recurrence of atrial arrhythmia. Recently, the novel DiamondTempTM (DT) ablation system was introduced and allows for high-power, short-duration ablation in a temperature-controlled mode. Its use during pulmonary vein isolation (PVI) using a recommended ablation setting with a catheter-tip temperature limit of 60°C, a temperature-controlled power of 50 W and an application duration of 10 sec has shown to be effective and safe. However, data on DT ablation settings for substrate modification, i.e., creation of linear lesions are lacking. Aim: The aim of the present study was to evaluate acute efficacy and safety of the novel DT ablation system for bidirectional block of the MIL using two different protocols. Methods: The study population comprised 14 patients [67±8 years, 10/14 male (71%)] suffering from persistent AF and/or atrial tachycardia who underwent catheter re-ablation with creation of a MIL using the DT ablation system. Ablation settings were a catheter-tip temperature limit of 60°C, a temperature-controlled power of 50 W with an application duration of either 10 sec (group A, n=7) or 20 sec (group B, n=7). Additional epicardial ablation from within the coronary sinus with a temperature limit of 60°C, a temperature-controlled power of 20 W and an application duration of 20 sec was performed, if bidirectional block could not be achieved with endocardial ablation only. Results: Mean procedure and fluoroscopy time, and dose area product for group A and group B were 103±24 vs. 119±38 min, 12±5 vs. 13±4 min, and 572±270 vs. 537±202 cGycm, respectively. Bidirectional block of the MIL was achieved in 7/7 (100%) patients in group A and in 6/7 (86%) patients in group B. Additional epicardial ablation was required in 6/7 patients (86%) in group A and in 4/7 (57%) patients in group B. In group B, bidirectional block of the MIL required fewer endocardial (31±11 vs. 26±10 applications) as well as epicardial RF-applications (10±6 vs. 7±3 applications). Pericardial effusion without hemodynamic relevance occurred in 1/7 (14%) patients of group B. No further complications occurred. Conclusion: Catheter ablation of the MIL using the novel DT ablation system is safe and associated with high acute efficacy. A lower number of RF-applications and a less frequent need for additional epicardial ablation was observed when applying longer RF-applications of 20 sec. Further analyses are warranted to confirm these findings.